Current Assets - eBooks and textbooks from bookboon.com - Walther, Larry M. (bookboon.com, 2016)
This book is the second of seven books which introduces the basic principles of accounting, focusing primarily on liquid assets. It introduces enhanced income statements, sales, cash discounts, the control structure, and inventory accounting. Details concerning cash and highly-liquid investments, cash management, controls for cash receipts and disbursements, and bank account reconciliations are discussed. Accounts receivable, costs and benefits of selling on credit, considerations for uncollectible receivables, notes receivable and interest are also discussed. In addition, the fundamentals of inventory costing methods, inventory management, and ratio analysis are introduced.